2022
DOI: 10.1108/mbr-05-2022-0080
|View full text |Cite
|
Sign up to set email alerts
|

Family firms and international equity-based entry modes: a systematic literature review

Abstract: Purpose Although research on family firms (FF) internationalization has seen a boom over the past 30 years, the understanding of how FFs internationalize with equity modes is still fragmented. Indeed, the majority of extant literature on this topic identifies internationalization with export, overlooking the alternative equity-based entry modes FFs have when entering a foreign country. The purpose of this paper is to fill this gap with a framework-based systematic literature review on the topic to improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Sestu et al (2018) combined the social-emotional wealth theory and transaction cost theory, and they found that the decision making of equity entry mode of Italian family and non-family firms would be affected by the family or non-family nature of local firms [49]. Other scholars (Sena et al, 2022;Maggi et al, 2023) examined institutional variables and multinational firms and were concerned about their equity entry mode [50,51].…”
Section: Research On Family Business and Equity Entry Mode In Oversea...mentioning
confidence: 99%
“…Sestu et al (2018) combined the social-emotional wealth theory and transaction cost theory, and they found that the decision making of equity entry mode of Italian family and non-family firms would be affected by the family or non-family nature of local firms [49]. Other scholars (Sena et al, 2022;Maggi et al, 2023) examined institutional variables and multinational firms and were concerned about their equity entry mode [50,51].…”
Section: Research On Family Business and Equity Entry Mode In Oversea...mentioning
confidence: 99%
“…The extent of ownership of multinational corporations in their foreign subsidiaries represents a critical decision as these corporations navigate the intricacies of global expansion. Significant research efforts have been directed towards investigating the factors influencing the levels of equity ownership in foreign subsidiaries (Bruneel & De Cock, 2016;Maggi et al, 2022). As the firm aims to penetrate new markets and engage with local customers, the selection of appropriate foreign market entry strategies becomes paramount.…”
Section: Foreign Market Entrymentioning
confidence: 99%
“…Inquiries into the determinants influencing the selection of equity ownership levels in foreign subsidiaries persist as a central focus within the realm of foreign market entry mode research. As evidenced by recent comprehensive reviews conducted by Chhabra et al (2021) and Maggi et al (2022), substantial scholarly attention is currently devoted to examining the factors shaping the extent of equity ownership in foreign subsidiaries. Various theoretical frameworks have been posited to elucidate the underlying rationale governing the decision-making process regarding equity ownership levels, encompassing perspectives such as the resource-based view (Barney, 1991), organizational learning theory (Barkema & Vermeulen, 1998), institutional 10 theory (Di Guardo et al, 2016), transaction cost economies (Williamson, 1986), and network theories (Birkinshaw & Pedersen, 2009;Rugman & Verbeke, 2001).…”
Section: Foreign Market Entrymentioning
confidence: 99%